Implementasi Algoritma Dijkstra untuk Rute Pengiriman Tahu di UMKM Pabrik Tahu Andra Sela - Pebriansyah, Dipta Wahyu; Astuti, Indah Puji; Sugianti, Sugianti (Universitas Muhammadiyah Ponorogo, 2025)
In the digital era, the efficiency of goods distribution has become a crucial factor for industries to ensure smooth operations. Small-scale industries, such as tofu factories in Demangan Village, Siman, Ponorogo, still face challenges in managing distribution and transactions. This study aims to develop a web-based system that implements Dijkstra's algorithm for tofu delivery route optimization and provides transaction management features to support the company's operational efficiency, ensuring its sustainability. The system development follows the Rapid Application Development (RAD) methodology, which emphasizes speed and efficiency through prototyping and rapid iterations. System testing is conducted using Dijkstra's algorithm and Black Box Testing. Dijkstra's algorithm is manually verified to ensure the system can determine the optimal route based on distance or travel time, while Black Box Testing is used to verify system functionality, including data insertion and updates, order processing, and route calculation. The test results show that the system can determine the shortest delivery route, reduce travel time, and minimize operational costs. Additionally, the system supports real-time transaction recording, ensures data accuracy, and provides systematic reports for evaluating distribution performance. Thus, this system proves to be effective in improving tofu distribution efficiency and assisting strategic decision-making.